PERAN IBU RUMAH TANGGA ANGGOTA GERAI KEMBANG SETAMAN TERHADAP EKONOMI KELUARGA DI KELURAHAN TIRTA SIAK KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Ernia, Yefsi; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The role of a housewife is the role played by a woman who is married or widowed. While the contribution is the amount of donations given in the form of material that is useful to help the economy in the family. This research was carried out in Sekolah Street, Tirta Siak Village, Payung Sekaki District. The purpose of this research is to find out the activities or roles carried out by housewives who are members of the Kelompok Usaha Bersama Ibu Kreatif Gerai Kembang Setaman, as well as within the Joint Business Group that they work on and possess, and to determine the contribution of housewife income ladder in helping his family income. This research uses descriptive quantitative method with total census / sampling technique where the respondents number as many as 58. Data collection techniques using observation methods, guided interviews using questionnaires, and documentation. The results showed that from these 12 KUB, housewives who joined in the faithful group mostly had the aim to increase family experience and income. And housewives members of this Joint Business Group contributed an average of 4.9% with an average income of Rp.202,672. And the lowest contribution given by housewives in Gerai Kembang Setaman has never contributed or 0%, then the highest contribution is 15% or Rp.900.000, this is obtained from the contribution of housewives in the Joint Business Group within one month. And each group has their agreed hours and days of business. And the place of sale of products is in the Gerai Kembang Setaman and is outside and inside the Gerai Kembang Setaman. Keywords : Role Of Housewife, Joint Business Group, Contribution